Dynamic contrast enhanced MRI of the placenta: A tool for prenatal diagnosis of placenta accreta?. (May 2017) - Millischer, A.E.; Deloison, B.; Silvera, S.; Ville, Y.; Boddaert, N.; Balvay, D.; Siauve, N.; Cuenod, C.A.; Tsatsaris, V.; Sentilhes, L.; Salomon, L.J.
Abstract: Background: Ultrasound (US) is the primary imaging modality for the diagnosis of placenta accreta, but it is not sufficiently accurate. MRI morphologic criteria have recently emerged as a useful tool in this setting, but their analysis is too subjective. Recent studies suggest that gadolinium enhancement may help to distinguish between the stretched myometrium and placenta within a scar area. However, objective MRI criteria are still required for prenatal diagnosis of placenta accreta. The purpose of this study was to assess the diagnostic value of dynamic contrast gadolinium enhancement (DCE) MRI patterns for placenta accreta. Materials and methods: MR images were acquired with a 1.5-T unit at 30–35 weeks of gestation in women with a history of Caesarian section, a low-lying anterior placenta, and US features compatible with placenta accreta. Sagittal, axial and coronal SSFP (Steady State Free Precession) sequences were acquired before injection. Then, contrast-enhanced dynamic T1-weighted images were acquired through the entire cross-sectional area of the placenta. Images were obtained sequentially at 10- to 14-s intervals for 2 min, beginning simultaneously with the bolus injection. Functional analysis was performed retrospectively, and tissular relative enhancement parameters were extracted from the recorded images. The suspected area of accreta (SAA) was placed in the region of the previous scar, and a control area (CA) of similar size was placed on the same image plane, as far as possible from the SAA. Semi-quantitative analysis of DCE-MR images was based on the kinetic enhancement curves in these two regions of interest (ROI). Three tissular relative enhancement parameters were compared according to the pregnancy outcomes, namely time to peak, maximal signal intensity, and area under the enhancement curve. Results: We studied 9 women (43%) with accreta and 12 women (57%) with a normal placenta. All three tissular relative enhancement parameters differed significantly between the two groups (p < 10 −3 ). Conclusion: The use of dynamic contrast-enhanced MRI at 30–35 weeks of gestation in women with a high risk of placenta accreta allows the extraction of tissular enhancement parameters that differ significantly between placenta accreta and normal placenta. It therefore provides objective parameters on which to base the diagnosis and patient management. Highlights: Usefulness of DCE MRI with tissular enhancement parameters. Particular heterogeneity of Abnormal Invasive Placenta. The homogeneity of normal placenta.